Կանոնական իրավունք եւ աստվածաբանություն. մոտեցումներ ու հեռանկարներ հայ եկեղեցական-կանոնական իրավունքի ավանդության լույսի ներքո - Անանյան, Տ. Շահե ծայրագույն վարդապետ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Изучение проблем церковно-канонического права Армянской Апостольской Церкви занимает особое место в историко-филологических исследованиях культуры христианского Востока. Начиная с XIX века западные и восточные специалисты в своих трудах в основном оценивали историко-филологическую важность памятников средневекового Армянского церковно-канонического права. Несмотря на немалое количество трудов и исследований, богословская оценка церковно-канонического права Армянской Апостольской Церкви все еще остается незначительной. Цель автора — систематизировать в данной статье вопросы и перспективы относительно богословской значимости и содержания традиции средневекового Армянского церковно-канонического права․ The study of problems with respect to the canon law of the Armenian Apostolic Church occupies a special place in the historical and philological studies of the culture of the Christian East. Starting from the 19th century, Western and Eastern specialists in their works mainly assessed the historical and philological importance of the monuments of medieval Armenian canon law. Despite a considerable amount of works and researches, the theological assessment of the canon law of the Armenian Apostolic Church still remains insignificant. Hence, a great number of questions touching on the theological content and meaning of the canon law are still waiting for scientific appraisal in the light of the Armenian Church tradition. The author’s goal in this article is to systematize questions and perspectives regarding the theological significance and content of the tradition of medieval Armenian canon law.
Keywords: Կրոնագիտություն; Հայոց եկեղեցի